Hubungan Tingkat Pengetahuan tentang Kehamilan tidak diinginkan dengan Perilaku Seksual Remaja di SMA N 6 Semarang - Hartiani Halawiyah; Mudy Oktiningrum; Nella Vallen (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The 2015 Central Java Indonesian Family Planning Association (Pilar PKBI) Youth Information and Services Survey revealed that with questions about the process of having a baby, family planning, ways to prevent HIV/AIDS, anaemia, ways to care for the reproductive organs, and knowledge of organ function reproduction, information was obtained that 43.22% had low knowledge, 37.28% knowledge was sufficient, and 19.50% knowledge was sufficient.A preliminary study at SMA Negeri 16 Semarang was conducted in January 2023, and the results showed that out of a total of ten students—five boys and five girls—seven were aware. Secondary data also supports the results of the preliminary study. According to interviews with the counselling teacher, a pair of students had kissed, hugged, and touched sensitive areas in the school area. The study aimed to determine the relationship between adolescents’ knowledge level about unwanted pregnancies and adolescent sexual behaviour at SMA Negeri 16 Semarang. The study aimed to determine the relationship between adolescents’ knowledge level about unwanted pregnancies and adolescent sexual behaviour at SMA Negeri 16 Semarang. type of research is observational with an analytic survey method; this study was designed using a cross-sectional approach. The population in this study was all 424 students. With sampel 81 students of SMAN 16 Semarang—retrieval using a purposive sampling technique. The statistical test used was the Chi-Square test. The research results obtained a p-value of 0.023 so that the p-value (0.023) α (0.05) So it can be concluded that there is a very strong relationship with the value of r 1 between Knowledge Level and Adolescent Sexual Behaviour at SMAN 16 Semarang. It is hoped that this research can motivate adolescents to increase their knowledge about unwanted pregnancies based on the research results reviewed.